Morphometry in the cytological evaluation of breast lesions and its diagnostic significance - Sujata Jetley; Beenish Bano; Shaan Khetrapal; Safia Rana; Zeeba S. Jairajpuri; Ajay Thakral; Arushi Gupta (MGM Journal of Medical Sciences)
Background: Fine-needle aspiration cytology is the primary method for evaluating patients with palpable breast lumps. The “gray zone” in breast cytology, where the distinction between benign and malignant lesions is unclear, is estimated to comprise 8.9% of cases. Nuclear morphometry, an objective tool that supplements cytological analysis, helps minimize subjective variations. Since nuclear structural alterations are key morphological indicators of cancer, nuclear morphometry, supported by image analysis, is crucial in delivering rapid and reproducible assessments. A study involving 100 cases was conducted at a Tertiary Care Hospital in New Delhi, India. Aims and Objectives: To perform a cytomorphological evaluation of fine-needle aspirates from breast lumps, apply nuclear morphometry to all cytological samples, compare the morphometric features across various breast lesions, and assess its effectiveness in distinguishing benign lesions from malignant ones. Study Design: Cross-sectional study. Materials and Methods: Cytological grading involves assessing cell dissociation, size, uniformity, the presence or absence of nucleoli, nuclear margins, and nuclear chromatin. Lesions are categorized into Grades I, II, and III. Smears were analyzed using computer-based cytomorphometry to measure nuclear and cytoplasmic parameters. The obtained values were, then, evaluated and correlated with histopathological findings. Results: A strong correlation between cytomorphometric parameters and histopathologically diagnosed benign, premalignant, and malignant categories was observed. Statistical analysis demonstrated significant discriminatory ability in predicting malignancy, with the nuclear-to-cytoplasmic (N:C) ratio showing the highest predictive accuracy. Conclusion: Aspiration cytology is an effective and convenient diagnostic method for the early detection of premalignant and malignant breast lesions. Combined with cytomorphometry, it aids in monitoring cellular transformations associated with these conditions.